(untitled) (MAUSAM, 2016)
Risk of extreme precipitation anomaly of Indian summer monsoon (ISM) on agro-ecosystems of Indo-Gangetic Plain (IGP) and central-east India regions has been assessed in the present study. Using monthly gridded precipitation data, standardized precipitation index (SPI) has been computed as the hazard component of the standard risk computation. The agro-ecosystems of IGP are exposed to higher risk due to extreme ISM precipitation anomaly than that of the central-east India. IGP being an irrigated region and central-east India being a rainfed region would be affected differentially due to the increasing negative anomaly in precipitation (i.e., drought risk) in the two regions. Overall the risk score and the prevalent agricultural practice suggest that the Central plateau and hill region in the rainfed region and the Upper Gangetic plain in the irrigated region are the most drought risk pone agroclimatic zones. Exceedance probability (EP) curve and the return period (RP) curve of drought risk quantification revealed that the Upper Gangetic plain of the IGP is conspicuously exposed to a higher drought risk unlike any other region. Increasing drought risk is coupled with increasing cloud cover in Upper Gangetic plain. Surface wind, temperature or the outgoing longwave radiation of this zone could not completely explain the cause of this risk. Changing role of average aerosol index (AAI) hinted to the presence of aerosol altered cloud micro-system in Upper Gangetic plain and may be one of the major reasons for increasing non-precipitating cloud in this zone and thus contributing to the drought risk even with increasing cloud cover trend.